The Evolution of the Insurance Consumer Protection Approach in Hungary - Banyár, József; Turi, Petra (Public Finance Quarterly, 2023)
The evolution of financial markets and the innovations that technology provides often bring about new threats and problems. Consumers often feel that they agreed to unfavourable terms and that only the service provider benefits from the contract they signed. This increases the importance of financial consumer protection, including insurance. Hungary was among the countries that were not satisfied with following international trends and adopting international solutions, it was one of the trailblazers as it independently introduced consumer protection solutions in insurance and finance. We are confident that the solutions introduced in Hungary are interesting for other countries, as well. Regulators usually did not choose textbook solutions, and they often did not take efforts to put them in a general theoretical context. In retrospect, however, we see a certain evolution of the principles and theory of consumer protection solutions in the insurance industry in Hungary. This study aims to explore this evolution through actual, specific solutions. Even though this is constructed retrospectively, we believe that to be able to move forward, this theoretical reflection is essential, and so is our effort to provide a sort of theoretical foundation for consumer protection in the insurance sector in Hungary, and the solutions that have been used to date are useful in this. We rely on these as we try to explore the best potential way forward.